Political Psychopathy : Fujimori case - Nizama Valladolid, Martin (2008)
Seven years after his political fall, Alberto Fujimori Fujimori was extradited from Chile on September 22 of 2007, in order to judge him by two cases of human rights violations and five corruption cases. The mega-trial begun on december 10 of 2007. According to the mediate authorship theory, having led the command in charge of the counterterrorist actions involves him in crimes related to human rights. The Supreme court special penal division judges him by six cases related to human rights, corruption and graft, divided in three mega-trials: 1) La Cantuta - Barrios Altos and the Gustavo Gorriti and Samuel Dyer kidnapping in the Military intelligence Service basements. 2) Phone-tapping, and TV channels and congress men bribing. 3) 15 million nuevos soles of payement to Montesinos as a time of service compensation. The last case, the unlawful entry into the house of Trinidad Becerra, Montesino´s ex-wife, is been treating apart because it is a summary process. However, AFF couldn´t have made it all alone. His criminal actions were orchestrated above the shadows of his collaborators, that had proceeded illegally, like a mafia organization. Furthermore, there is presented a systematization of the psychopathologic trama of this intrincated political affair, that configures a psychopathic syndrome which predictable evolution will mean the end of the yearned impunity that AFF is looking for.